A siloxane-incorporated copolymer as an in situ cross-linkable binder for high performance silicon anodes in Li-ion batteries. Issue 17 (18th April 2016) - Jeena, M. T.; Bok, Taesoo; Kim, Si Hoon; Park, Sooham; Kim, Ju-Young; Park, Soojin; Ryu, Ja-Hyoung
Abstract : An in situ crosslinkable siloxane-incorporated polymeric binder has been developed for Si anodes in Li-ion batteries. The binder showed stable cycle retention with a specific capacity of 2551 mA h g −1 over hundred cycles with an initial columbic efficiency of 81%. Abstract : The electrochemical performance of Li-ion batteries (LIBs) can be highly tuned by various factors including the morphology of the anode material, the nature of the electrolyte, the binding material, and the percentage of conducting materials. Binding materials have been of particular interest to researchers over the decades as a means to further improve the cycle durability and columbic efficiency of LIBs. Such approaches include the introduction of different polymeric binders such as poly(acrylic acid) (PAA), carboxymethyl cellulose (CMC), and alginic acid (Alg) into the Si anode of LIBs. To achieve a better efficiency of LIBs, herein, we introduce a novel copolymer, poly( tert -butyl acrylate- co -triethoxyvinylsilane) (TBA-TEVS), as an efficient binder with stable cycle retention and excellent specific capacity. The binder forms a highly interconnected three-dimensional network upon thermal treatment as a result of de-protection of the tert -butyl group and the consequent inter–intra condensation reaction, which minimizes pulverization of the Si nanoparticles. Moreover, the siloxane group is expected to promote the formation of stable solid-electrolyte–interface (SEI) layers. A series of random copolymers were synthesized by varying the molar ratio of tert -butyl acrylate and triethoxyvinylsilane. Twenty-one percent of TEVS in the TBS-TEVS copolymer gave rise to a superior performance as a binder for Si anodes, where the anodes showed a stable specific capacity of 2551 mA h g −1 over hundreds of cycles and an initial columbic efficiency (ICE) of 81.8%.